Upaya Mengurangi Ketergantungan Gadget pada Peserta Didik Kelas IV dalam Proses Pembelajaran dengan Menggunakan Media Powerpoint di UPTD SDN Keleyan 1 Bangkalan - Fatimah Azzahra (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2023)
Flexible learning which is a characteristic of the Independent Curriculum, requires educators to make learning with the use of technology. One of them is through gadgets that can be applied by all ages. However, gadgets also have a bad influence on students, one of which is dependence on gadgets during learning activities. For this reason, the purpose of this research is to reduce gadget dependence by fourth grade students at UPTD SDN Keleyan 1 with a solution of providing a powerpoint learning media in Indonesian. The number of subjects in this study were 18 students. Instrument techniques and data collection in this study included interviews, observations, questionnaires and tests. The data analysis technique used is descriptive quantitative. The results of the study show that PowerPoint learning media can be a solution when fourth grade students at UPTD SDN Keleyan 1 are dependent on gadgets during the learning process, especially during Indonesian lessons. Classroom Action Research (CAR) with the implementation of the first cycle obtained an average result of the powerpoint learning media satisfaction questionnaire of 86% and the second cycle obtained an average powerpoint learning media satisfaction questionnaire result of 91%. So that in cycle II it has reached the desired result criteria of the researcher which is equal to 90%.